Integrated Environment for Software Documentation - Ahmed Sullabi, Mohamed (2000)
Software documentation refers to the information on the various phases of the software. It includes design specification, performance specification, functional specification, source code information, development information, etc. The source code documentation represents the collection of documents that explains, describes the functions, structures, inputs, outputs, etc., and defines the purposes and uses of a particular software program. Good documentation is the major difficulty of creating a good software and the software project cannot succeed without documentation. Unfortunately, it is quite often no technical documentation is produced. In addition, when documentation is produced, it is often poorly or incompletely written, and may not be kept current. Those factors contribute to the reasons for software failures, to the difficulty of maintaining the software at a later time, or to the high overhead into subsequent product development. The objective of the research is to provide software developers with a useful practical environment for their performance improvement. This environment is an integrated environment that concentrates on solving some of the existing problems, which discourage software developers to document their work; mainly, documentation costs time due to the separation between the software development area and software documentation area, when the programmers should document, and what they should document. The integrated environment will frrstly, provide an encouragement environment for software developers to document their work by combining the development and documentation environments into one environment, and this combination will ease the movement between the two environments in order to reduce the time needed. Secondly, it will integrate the facilities needed to manage the software project and to help the developers determine when documentation should be written and what should be written. The integrated environment has been implemented in a tool called IESD (Integrated Environment for Software Documentation).The tool was evaluated by a group of postgraduate students to test the workability, usability, and reliability of the system, and verify whether the system had achieved its objectives. Questionnaires were distributed to the students. The analysis of the student responses had shown out that the tool was very useful and easy to use, and the rate of agreement was over 80%.Based on this study, it can be concluded that the integration between the programming environment and the documentation environment with the facilities provided, has helped the users to tackle the crucial problems of documentation.